Numerical Analysis of Slope Stability with Nailing Method Using Bamboo as Nailing Material - Sharfaraj Khadem; Taskid Asif; Shafiqul Islam; Muhaimeen Rashid; Sandip Roy (Computational Engineering and Physical Modeling)
The fatality of a slope failure is devastating; slope stabilization methods are adopted to prevent such an incident. Nailing is known as one of the most used methods of slope stabilization. This research study has been conducted to observe the increment of stability of natural slopes by the nailing method. Here, bamboo is selected as an eco-friendly material for nailing. The stability analysis of slopes is conducted by numerical analysis. Finite element analysis is performed with PLAXIS 2D. The soft Soil model and Mohr-Coulomb model are used to define soil parameters. A comparison of these two soil models is also a concern of this study. The slope is modeled according to the natural slope. The stability analysis is conducted for five slope angles: 20⁰, 25⁰, 30⁰, 35⁰, and 40⁰. It is observed that the increase in slope angle factor of safety (FOS) decreases. Inserting nailing material as soil reinforcement increases the stability of the steeper slopes. Mild slopes usually remain stable in bare conditions; however, nailing improves that stability. Increased stability is observed more in this study for steep slopes. After nailing, the factor of safety increases by up to 21% for 20-30 degree slopes and up to 36 % for 30-40 degree slopes. It is expected that professional engineers will find this paper helpful while treating a slope with the nailing method.